(untitled) (Nativa, 2024)
This paper determined the best formulation of culture medium based on Kombucha tea and infusion of coffee husk for producing bacterial cellulose (BC) from Acetobacter xylinum. The highest BC production corresponded to the medium containing tea, coffee husk infusion, sugar and 0.005% methionine. This greater production occurred when the inoculum was kept in the dark, which allowed high multiplication of the microorganisms and, therefore, greater polymer production. Introducing a new, feasible, malleable material from an environmentally friendly process will allow the replacement of materials with a greater impact on pollution and cost. Keywords: Acetobacter xylinum; biomaterials; bacterial cellulose; coffee husk; Kombucha. Produção de celulose bacteriana a partir de infusão de chá de kombuchá e casca de café RESUMO: Neste artigo foi determinada a melhor formulação de meio de cultura à base de chá de Kombuchá e infusão de casca de café para produção de celulose bacteriana (BC) de Acetobacter xylinum. A maior produção de CB correspondeu ao meio contendo chá, infusão de casca de café, açúcar e 0,005% de metionina. Essa maior produção ocorreu quando o inóculo foi mantido no escuro, o que permitiu alta multiplicação dos microrganismos e, portanto, maior produção do polímero. A introdução de um novo material viável, maleável e proveniente de um processo amigo do ambiente permitirá a substituição de materiais com maior impacto na poluição e no custo. Palavras-chave: Acetobacter xylinum; biomateriais; celulose bacteriana; casca de café; Kombuchá.